2019
DOI: 10.1080/02813432.2019.1684426
|View full text |Cite
|
Sign up to set email alerts
|

Variations in older people’s use of general practitioner consultations and the relationship with mortality rate in Vantaa, Finland in 2003–2014

Abstract: Objective: It is generally expected that the growth of the older population will lead to an increase in the use of health care services. The aim was to examine the changes in the number of visits made to general practitioners (GP) by the older age groups, and whether such changes were associated with changes in mortality rates. Design and setting: A register-based observational study in a Finnish city where a significant increase in the older population took place from 2003 to 2014. The number of GP visits mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Further, previous Finnish studies have reported that the number of appointments per GP has generally decreased in PHC [14,37]. During the last decades, this decrease has not been evident in the oldest age cohorts [17]. There was no increase in the other studied types of consultations either.…”
Section: Comparison With Existing Literaturementioning
confidence: 67%
See 2 more Smart Citations
“…Further, previous Finnish studies have reported that the number of appointments per GP has generally decreased in PHC [14,37]. During the last decades, this decrease has not been evident in the oldest age cohorts [17]. There was no increase in the other studied types of consultations either.…”
Section: Comparison With Existing Literaturementioning
confidence: 67%
“…It has been suggested that if PHC is unavailable, more urgent treatment-oriented sites of healthcare are forced to back-up its functions [29,30]. In line with this, when PHC started to have difficulties maintaining its normal non-urgent services during the last years of nGP [14,17], non-urgent scheduled appointments were compensated for by urgent ones, although appointments at the emergency department per se were not affected in the study population.…”
Section: Comparison With Existing Literaturementioning
confidence: 87%
See 1 more Smart Citation
“…However, in the studied age groups 20–64 and 65+ the mortality tended to decrease [ 18 ]. Only a slight plateauing of the decreasing monthly mortality was observed in the oldest age group (65+) after 2008, the year of the implementation of “reverse triage”, [ 5 ] but analogous plateauing was observed in the mortality of the whole Finnish 65+ age group in the period 2008–2014 [ 20 ]. Thus, no lethal safety hazards were found in this analysis.…”
Section: Discussionmentioning
confidence: 99%